Renewal of terms in the course of the administrative proceeding as the court’s discretionary powers - Moroz , Svitlana; Riabchenko Оlena (Archives of Criminology and Forensic Sciences, 2023)
The problematics of the topic of Renewal of terms in the course of the administrative proceeding as a discretionary power of the court is due to the absence of a legal definition for the grounds and conditions of renewing missed terms, the need for scientific and practical research concerning the practical implementation of courts’ discretionary powers during term renewal, and the identification of specific problems with their potential solutions. The Article Purpose is to define the concept of the court’s discretionary powers, to form an understanding of the practical implementation of the court’s discretionary powers during the renewal of procedural terms in the course of administrative proceedings, as well as to single out practical issues. We have determined that the courts’ discretionary powers regarding term renewal stem from their authority to decide, at their discretion, both the issue of renewing the procedural term and whether the parties truly have had valid reasons for missing it. It has been conluded that currently the practical implementation of the discretionary powers by the court in terms of renewal of terms is as follows: 1) the court’s interpretation of omission of a procedural term by a party as acting in bad faith; 2) the inability by the party to prove validity of reasons for omission on the basis of the criteria established by judicial practice: - objectively insurmountable circumstances; - circumstances that are beyond the party’s control; - real obstacles and difficulties; 3) the party’s inability to substantiate the validity of reasons for omitting the procedural term with an adequate body of evidence. 4) determination by the court of term renewal as a breach of legal certainty. At present, to address the outlined challenges in the practical implementation of discretionary powers when renewing procedural terms in administrative proceedings, we see a solution in the formation by the Supreme Court of a sustainable judicial practice. It includes establishing a unified approach to handling such cases and embedding a standardized interpretation of the grounds for renewing procedural terms in judicial practice. The development of a sustainable judicial practice by the Supreme Court will prevent courts of other instances from interpreting and applying grounds for term renewal in an ambiguous manner.